MANAGING STATE OF DESPAIR IN CARDIAC PATIENTS BY INCREASING THEIR DIGNITY AND SPIRITUAL WELLBEING THROUGH PEACE THERAPY - Sarwat Sultan; Mehreen Fatima Ahmad; Sabahat Nawaz; Aqsa Batool; Komal Riaz (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This study investigates the impact of PEACE therapy (Positive Emotions after Acute Cardiac Events) on psychological outcomes in hypertensive heart disease patients. A repeated measures design was employed with a sample of 20 outpatients aged 42-53 from the Institute of Cardiology, Multan, Pakistan. Participants were randomly assigned to either an intervention group (n=10) receiving PEACE therapy sessions or a control group (n=10). Pre- and post-therapy data were collected on measures of dignity, spiritual wellbeing, depression, hopelessness, and desire for death. Results indicate significant improvements in the intervention group compared to the control group. Specifically, patients in the intervention group reported decreased levels of depression, hopelessness, and desire for death, alongside enhanced dignity and spiritual wellbeing. Conversely, the control group exhibited increased psychological distress over the study period. These findings advocate the efficacy of PEACE therapy in enhancing psychological wellbeing among cardiac patients. By addressing psychological factors such as depression and hopelessness through dignified and spiritually-focused interventions, PEACE therapy proves beneficial in mitigating psychological distress associated with cardiac illness.